Motion-towards-each-other-based hand gesture initialization. Issue 12 (December 2015) - Feng, Zhiquan; Yang, Bo; Lv, Na; Xu, Tao; Yin, Jianqin; Zhao, Xiuyang; Feng, Shichang
Abstract Initialization for a 3D hand model is significant in determining a 3D hand model that corresponds to a user׳s 3D hand pose in the initial frame. We propose a motion-towards-each-other-based human–computer cooperation algorithm with the aim to reduce the operational burden on the user and cause the computer׳s response to the user׳s operation to fall within acceptable scopes. The computer first recognizes the user׳s interactive intentions through the hand gesture sensing algorithm and at last cooperates with the user until they achieve the meeting point. The main contributions of this study are sensing the operator׳s interactive intentions and focusing on the motion-towards-each-other-based interactive cooperation mechanisms between a human and a computer to achieve low cognitive and operational burdens. The proposed approach can effectively reduce users׳ cognitive and operational burdens. The proposed initialization system is successfully applied to several application systems.